Chemically and Biologically Harmless versus Harmful Ferritin/Copper–Metallothionein Couples. Issue 2 (4th November 2014) - Carmona, Fernando; Mendoza, Daniela; Kord, Scheghajegh; Asperti, Michela; Arosio, Paolo; Atrian, Sílvia; Capdevila, Mercè; Dominguez‐Vera, Jose M.
Abstract The simultaneous measurement of the decrease of available FeII ions and the increase of available FeIII ions allowed the analysis of the ferroxidase activity of two distinct apoferritins. Although recombinant human apoferritin (HuFtH) rapidly oxidizes FeII to FeIII, this iron is not properly stored in the ferritin cavity, as otherwise occurs in horse‐spleen H/L‐apoferritin (HsFt; H=heavy subunit, L=light subunit). Iron storage in these apoferritins was also studied in the presence of two copper‐loaded mammalian metallothioneins (MT2 and MT3), a scenario that occurs in different brain‐cell types. For HuFtH, unstored FeIII ions trigger the oxidation of Cu–MT2 with concomitant CuI release. In contrast, there is no reaction with Cu–MT2 in the case of HsFt. Similarly, Cu–MT3 does not react during either HuFtH or HsFt iron reconstitution. Significantly, the combination of ferritin and metallothionein isoforms reported in glia and neuronal cells are precisely those combinations that avoid a harmful release of FeII and CuI ions.